Sustainable and Inclusive Finance in Turkey - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2017)
For strong and sustainable growth finance must be inclusive. Individuals and companies should have equal opportunity on accessing markets and resources. Financial inclusion does not mean pushing access for the sake of access, and it certainly does not mean making everybody borrow. For inclusive economic development, inclusive finance is a necessary criteria. Growth becomes inclusive if it is supported by structural reforms. The main purpose of this chapter is to explore the terms of sustainable and inclusive finance and assess the underlying role in the developing countries especially in Turkey and to reveal the current situation and further possibilities.